Small-scale Fishermen along the Naaf River, Bangladesh in Crisis: A framework for management - Chowdhury , M.S.N.; Hossain , M.S.; Das , N.G.; Barua , P. (Mesopotamian Journal of Marine Sciences, 2022)
Fishing is the most important traditional economic activity of the coastal communities in Bangladesh due to the availability of the diverse fishery resources. The Naaf River estuary is one of the large estuaries in Bangladesh coast, which plays a significant role in the socioeconomic condition of local community and considered as a major source of income through small-scale fishing. This paper highlights d the chronic problems and relative actions through sustainable management of small-scale fishermen of Naaf river. Community based participatory approach (PRA/RRA) was used for semi-structured questionnaire interviews of 120 small-scale fishermen from the three fishing communities soliciting information on their activities, financial flows and the main problems confronting their enterprise. Furthermore, 24 focus group discussions were arranged with different stakeholders to collect data on the organization and management of small-scale fishing as well as to get their opinions on the problems, causes and their consequences. The present study revealed that local communities in Teknaf coast are highly dependent on fisheries resources of the Naaf River. Major problems identified within the fishing community were high dependency to fishery resources, annual catch reduction, catch price fluctuation, by catch discard, lack of processing and preservation facilities, credit facilities, and training supports resulting in a disorganized fishing community with poor economic return. To ensure the sustainability, the fisheries sector need to overcome these increasing problems through management plan focusing on optimum fishery resources exploitation taking into account the top down and bottom up views of different stakeholders, “Community Based Fisheries Co-management” framework has formulated for long term sustainability and livelihood security of local community. This will go along way to help sustain the coastal fisheries resources with active participation of the fishermen.